Treatment of class I maloclusion with positive tooth arc discrepancy - Pari Cruz, Nilo Marcial (2021)
The objective of the case report was to evaluate the orthodontic treatment of a Class I malocclusion with positive tooth arch discrepancy in a 15-year-old patient, who, after alignment and leveling of the dental arches, underwent treatments, with resin stops for lifting of bite, reverse curve arches, upper and lower retraction arches for the closure of spaces and, finally, intermaxillary elastics for good intercuspation. After 17 months of treatment, the molar and canine Class I relationship was maintained, the diastemas were closed, the midline, the overjet and overbite were corrected, and a pleasant dental and facial esthetics were obtained. The various treatment alternatives in a Class I malocclusion depend on factors such as the severity of the malocclusion, etiology and others, in order to obtain a functional masticatory system and good aesthetics.